Advances in Information Systems Development New Methods and Practice for the Networked Society Volume 2 - Maygar, Gabor; Knapp, Gabor; Wojtkowski, Wita; Wojtkowski, Gregory; Zupancic, Jože (Springer US : Imprint: Springer, 2007)
Advances in Information Systems Development: Bridging the Gap between Academia and Industry, Volumes 1 and 2, are the collected proceedings of the Fourteenth International Conference on Information Systems Development: Methods and Tools, Theory and Practice - ISD'2005 Conference. These latest volumes on Information Systems Development examine the exchange of ideas between academia and industry and aims to explore new solutions. The field of Information Systems Development (ISD) progresses rapidly, continually creating new challenges for the professionals involved. New concepts, approaches and techniques of systems development emerge constantly in this field. The seven conference tracks highlighted at the Fourteenth International Conference on Information Systems Development - ISD'2005 Conference: - Co-design of Business and IT - Communication and Methods - Human Values of Information Technology - Service Development and IT - Requirements Engineering in the IS Life-Cycle - Semantic Web Approaches and Applications - Management and IT.